Bilirubin, Renal Hemodynamics, and Blood Pressure - Stec, David E.; Hosick, Peter A.; Granger, Joey P. (Frontiers in Pharmacology, 2012)
Bilirubin is generated from the breakdown of heme by heme oxygenase and the reduction of biliverdin by the enzyme biliverdin reductase. Several large population studies have reported a significant inverse correlation between plasma bilirubin levels and the incidence of cardiovascular disease. Protection from cardiovascular disease is also observed in patients with Gilbert’s syndrome which is a disease characterized by mutations in hepatic UGT1A1, the enzyme responsible for the conjugation of bilirubin into the bile. Despite the strong correlation between plasma bilirubin levels and the protection from cardiovascular disease, the mechanism by which increases in plasma bilirubin acts to protect against cardiovascular disease is unknown. Since the chronic antihypertensive actions of bilirubin are likely due to its renal actions, the effects of moderate increases in plasma bilirubin on renal hemodynamics as well as bilirubin’s potential effects on renal tubule function will be discussed in this review. Mechanisms of action as well as the potential for antihypertensive therapies targeting moderate increases in plasma bilirubin levels will also be highlighted.